Antena Mikrostrip dengan Dua Buah U-Slot untuk Aplikasi Wi-Fi dan 5G - Dian Widi Astuti; Alya Patrakomala; Muslim Muslim; Said Attamimi; Dwi Astuti Cahyasiwi (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2022)
The development of telecommunications on wireless networks is advancing very rapidly. This rapid development is caused by the need for rapid information accessible from anywhere. One of the devices on the wireless network telecommunications system is an antenna. Antennas that can work on multiple wireless network frequencies on telecommunications system devices are indispensable. Therefore, this study proposes the design of a microstrip antenna capable of simultaneously working on two wireless network frequencies, namely Wi-Fi and fifth-generation cellular telecommunications (5G). The microstrip antenna was designed using two slots, i.e., the disconnected rectangular ring and inverted U-shaped slots. The Wi-Fi and 5G frequencies working on this antenna were 2.45 GHz and 3.3 GHz. The resonant frequency on the antenna of this microstrip was affected by the slot length. The antenna was designed and fabricated using a Rogers 5880 substrate with a material’s relative permeability (er) of 2.2, a tangent loss (d) of 0.0009, and a thickness of 1.575 mm. Before being fabricated, the antenna design was simulated using the Ansys HFSS simulator, which is a simulator for designing components using electromagnetic waves including antennas. Compared to the simulation results, the results of reflection coefficient measurement in this antenna design showed excellent results for both frequencies. In the simulation results, the reflection coefficient provided a bandwidth of 123 MHz in the 2,412-2,535 MHz frequency range, while the measurement results provided a bandwidth value of 153 MHz in the 2,402-2,555 MHz frequency range for the Wi-Fi frequency application. At the 5G frequency, a measuring bandwidth of 87 MHz was obtained in the range of 3,260-3,347 MHz. The measurement results were commensurate with the simulation results, which obtained a bandwidth of 88 MHz in the range of 3,248-3,336 MHz. Therefore, the fabrication of this antenna design can be used for both applications.